Analytical simulation of Darcy-Forchheimer flow of hybrid nanofluid through cone with nonlinear heat source and chemical reaction - Khan, Husna A.; Nazeer, Ghazala; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2024)
This paper intends to discuss the hybrid nanofluid flow through a cone in a Darcy-Forchheimer porous media, containing base fluid Methanol (CH3OH), nanoparticles of titanium oxide (TiO2) and copper (Cu). We have examined the flow under the influences of mixed convection, viscous dissipation, chemical reaction, and nonlinear heat source. In hybrid nanofluid flow, viscous dissipation and mixed convection play a crucial role in heat exchangers. By accounting for both mixed convection and viscous dissipation, the addition of nanoparticles into a base fluid improves the transfer of heat and optimizes the performance of the cooling system. Using the laws of conservation, governing equations have been constructed. The flow model is converted using the appropriate similarity transformations from partial differential equations to ordinary differential equations. The homotopy analysis method is used to solve the updated system of equations. When Forchheimer inertial drag parameter is increased, the velocity profile decreases, but it rises when the Darcy number is increased. As the value of exponential heat source parameter rises, the temperature profile increases as well. The result exposes that with an increment in nanoparticle volume fraction, temperature profile also rises but velocity profile decreases.
Keywords: Viscous dissipation; hybrid nanofluid; Darcy-Forchheimer flow; vertical cone; chemical reaction; heat source/sink